Integrated time‐lapse geoelectrical imaging of wetland hydrological processes. Issue 3 (4th March 2016) - Uhlemann, S.S.; Sorensen, J. P. R.; House, A. R.; Wilkinson, P. B.; Roberts, C.; Gooddy, D. C.; Binley, A. M.; Chambers, J. E.
Abstract: Wetlands provide crucial habitats, are critical in the global carbon cycle, and act as key biogeochemical and hydrological buffers. The effectiveness of these services is mainly controlled by hydrological processes, which can be highly variable both spatially and temporally due to structural complexity and seasonality. Spatial analysis of 2‐D geoelectrical monitoring data integrated into the interpretation of conventional hydrological data has been implemented to provide a detailed understanding of hydrological processes in a riparian wetland. A two‐layered hydrological system was observed in the peat. In the lower part of the peat, upwelling of deeper groundwater from underlying deposits was considered the driver for a 30% increase in peat resistivity during Winter/Spring. In Spring/Summer there was a 60% decrease in resistivity in the near‐surface peats due to plant transpiration and/or microbial activity. Water exchange between the layers only appeared to be initiated following large drops in the encircling surface water stage. For the first time, we demonstrated that automated interpretation of geoelectrical data can be used to quantify ground movement in the vertical direction. Here, we applied this method to quantify shrink‐swell of expandable soils, affecting hydrological parameters, such as, porosity and permeability. This study shows that an integrated interpretation of hydrological and geophysical data can significantly improve the understanding of wetland hydrological processes. Potentially, this approach can provide the basis for the evaluation of ecosystem services and may aid in the optimization of wetland management strategies. Key Points: Characterization of wetland hydrological processes by resistivity monitoring Highlight seasonally dependent, layered groundwater system Quantification of peat shrink‐swell by edge detection applied to ERI data